Maternal mortality due to abortion complications in forcibly displaced populations: A study protocol for a community-facility capture-recapture (CFCR) study - Blake Erhardt-Ohren; Dipika Paul; Anik Mahmud; Anika Tarannum; Karen Weidert; Altaf Hossain; Sayed Rubayet; Ndola Prata (PLoS ONE, 2025)
There is a paucity of research exploring abortion complication-related morbidity and mortality in humanitarian settings. The most recent data we have to understand the impact of global negligence on forcibly displaced persons’ reproductive health needs in humanitarian emergencies is from the 1999 United Nations Population Fund’s annual report, which estimated that 25-50% of maternal deaths in refugee settings were due to complications from unsafe abortion. This study will investigate maternal death surveillance and reporting (MDSR). The protocol will be implemented in a refugee setting: Forcibly Displaced Myanmar National (FDMN) camps in Cox’s Bazar, Bangladesh. We will review death records for the past twelve months to learn more about how deaths are reported and recorded in facilities and in the camp-in-charge (CiC) office. Following the record review, we will interview individuals who provide reproductive healthcare services to FDMN and participate in MDSR where FDMN reside. These interviews will provide context and depth to the maternal death record review. We will implement a novel community-facility capture-recapture (CFCR) methodology to estimate maternal mortality. This research will fill a gap in knowledge about menstrual regulation, safe abortion and post-abortion access and care, and the measurement of maternal death due to abortion-related complications. This study will provide insights into a new opportunity to potentially more accurately measure maternal mortality due to abortion complications in these settings. The evidence gathered in the course of this research may assist global health practitioners in targeting interventions to prevent unsafe abortion and increase access to safe services that are tailored to forcibly displaced populations. The University of California, Berkeley Center for Protection of Human Subjects (CPHS # 2016-04-8614) and the National Research Ethics Committee (NREC) of the Bangladesh Medical Research Council (BMRC) (Registration # 578 10 03 2024) approved this study protocol.